A Conceptual Framework for Enhancing Academic Research Writing: Integrating Context-Specific Guidance and Swale’s CARs Model - Paramboor, Jafar; Effendi Kamaruddin, Ahmad Kamal; Al-Hudawi, Shafeeq Hussain Vazhathodi (Journal of Languages and Language Teaching, 2025)
Academic research writing (ARW) is a complex, epistemic, and disciplinary practice fundamental to postgraduate scholarship. Despite its centrality in higher education, novice researchers (NRs) often face persistent challenges, including limited epistemological awareness, difficulties with disciplinary conventions, and inadequate pedagogical support. This study addresses these gaps by proposing a conceptual framework that integrates Swales’ Create a Research Space (CARS) model with context-specific guidance to enhance ARW instruction. A narrative review methodology was employed to synthesize research on four core domains: content, context, language and structure, and cognitive ability. These constituent characteristics were mapped against common difficulties experienced by NRs and aligned with pedagogical strategies for scaffolding academic writing. The findings underscore the need for inclusive and responsive writing instruction that supports epistemic development and academic identity formation. The framework offers practical implications for writing curriculum design, mentoring, and instructional interventions. It also lays the groundwork for future empirical research to test its efficacy across varied educational contexts.